#### Answer

$F$

#### Work Step by Step

To solve the quadratic equation, we first need to factor the expression.
In order to do so, we first find two numbers that add to $2$ (the coefficient of the $x$-term) and multiply to $–3$ (the constant term).
These numbers are $3$ and $–1$, because $3 + (–1) = 2$ and $3(–1) = –3$.
Therefore:
$x^{2}+2x–3 = (x + 3)(x– 1)$
And our equation is now:
$(x + 3)(x– 1) = 0$
This means that either $x + 3 = 0$ or $ x – 1 = 0$ (by Zero Product Property).
Solving each of these for $x$, our solutions become:
$x = –3$ and $x = 1$